Olá marketing plan: the launching of an ice cream for the senior market - Martins, Luis Carlos da Silva (2011)
This master project has the objective to develop a marketing strategic and operational plan to support the launching of a range of ice cream products specifically designed to target to the senior consumer. This range of products will be launched in the Portuguese market by Olá during the summer of 2012. In this project we have identified the potential market and verified the value of the new product for Olá. To achieve this we made a strategic and operational study that will allow to evaluate the impact the new product will have for the brand and what will be the need of resources to implement the project. A marketing strategy was defined and marketing-mix components were designed to create an ice cream that will respond effectively to the senior needs. Finally, we provided several insights about senior consumer and his needs. We adapted this new range of products to what we find as the expectations of senior people about the ice cream category and Olá.